Exploring the cultural intelligence levels of bilinguals and multilinguals - Aksak, Kübra; Çubukçu, Feryal (Glottodidactica, 2023)
There have been numerous studies conducted on the importance of multiple intelligence levels of learners and the significance of language learning. By contrast, this study dwells on exploring cultural intelligence, its components and the relationship between cultural intelligence and language learning. To achieve this aim, bilingual and multilingual primary school students were selected and administered a cultural intelligence questionnaire to detect whether or not there is a relationship between these two aspects. The results yield the fact that multilinguals have higher scores in cultural intelligence, showcasing that those who are open to other cultures and can easily adapt to new patterns of thinking are likely to learn languages with ease.